Pendampingan Pengelolaan Keuangan dan Pembukuan Sederhana Pada Toko Kelontong Di Desa Ciwalen Kecamatan Garut Kota Kabupaten Garut - yoppy palupi (Universitas Majalengka, 2023)
Business actors carried out by individuals have increased every year. Business actors carry out activities of providing services, opening basic food and grocery stores that sell daily necessities as well as creating creative and other products. The increase in business actors carried out by individuals is not accompanied by an increase in the financial aspect. This is due to the lack of motivation and ability of business actors in managing their business finances. In addition, business actors have not been able to carry out financial records and bookkeeping properly and as a result, personal assets and company assets are often mixed into one. Another problem is the increasing competition with minimarkets, which are growing very rapidly, so that many people switch to shopping at minimarkets instead of shopping at grocery stores. As a result of this competition, the grocery store became empty of enthusiasts and ended up going bankrupt. Methods The implementation of the socialization work program for the financial management of the grocery store business in Ciwalen Village went through several stages starting with the observation stage. The results show that business actors have begun to realize the importance of managing business financial books and can make financial reports according to standards, these standard financial reports are used by third parties (taxes and banks) for banks to easily provide assistance for the smooth running of the business. .